The Value Connection - Gerstein, Marc H. (Wiley, 2003)
The Value Connection is aimed at serious investors who seek a systematic, structured approach to building and maintaining equity portfolios. It provides a flexible framework to select good stocks and–perhaps more important–it includes a disciplined approach to the critical hold vs. sell decision. Investors who follow the methodology detailed in The Value Connection will find themselves better organized, more focused, and ultimately more successful